Existence Theorems for Solvability of a Functional Equation Arising in Dynamic Programming - Deepmala (International Journal of Mathematics and Mathematical Sciences, 2014)
The paper deals with the existence, uniqueness, and iterative approximations of solutions for the functional equations arising in dynamic programming of multistage decision making processes in Banach spaces BC(S) and B(S) and complete metric space BB(S), respectively. Our main results extend, improve, and generalize the results due to several authors. Some examples are also given to demonstrate the advantage of our results over existing one in the literature.